Sistem Inventory Berbasis Web pada Usaha Konveksi Dona - Nuke Sairah Syabrina; Harfebi Fryonanda (UNIVERSITAS KALBIS, 2022)
Convection Dona is a home-based business that is engaged in the field of school needs, namely socks. The problem that occurs in the current system is the management of data items that are done manually that is recorded in a book that often results in loss of books. So it must be re-recorded. Where incoming goods come from employee packaging and outgoing goods come from konsumen purchases. Using the Prototyping method, Unified Design Language (UML) system modeling, and Black Box Testing, the purpose of this study is to create a Web-Based Inventory System capable of managing incoming and outgoing items. This system controls data regarding arriving and outgoing items, inventory, incoming and outgoing transactions, and can generate reports and accept online orders for goods.